Implementasi Sistem Informasi Manajaemen Keuangan Berbasis Web di SMA Cendana Pekanbaru - Maharani; Sohiron (EL-EMIR Institute, 2024)
This study aims to determine how the Implementation of Web-Based Financial Management Information System at SMA Cendana Pekanbaru. This type of research is conducted using a descriptive Qualitative research method. Overall, the informants involved in this study consisted of 2 people. Research data was obtained by interview, observation and documentation techniques. The results of this study are that the Implementation of Web-Based Financial Management Information System at SMA Cendana Pekanbaru has been implemented well. This is indicated by the existence of a Web System in school fee payment activities. Furthermore, the process of Implementing this Web-Based Financial Management Information System has been implemented several years ago. And will continue to be implemented and increasingly improved. Furthermore, the service at this school is also quite good, so that when there is an obstacle for parents in using the system, the administrative staff are ready to help serve. The supporting and inhibiting factors in the implementation of this web-based financial management information system are marked by the existence of sufficient funds, then human resources, where the parties involved in this institution have quite good quality. For inhibiting factors, it is not so difficult for external parties to use, it just takes more education to understand the web system.